Śrī-Śaṅkarāchārya's miscellaneous works = Śrīśāṅkarabhagavatpādīya prakaraṇaprabandhāvaliḥ - Śaṅkarācārya (Government Oriental Library series. Bibliotheca Sanskrita ;, 1899)
Miscellaneous works of Śaṅkarācārya.